1975
DOI: 10.3181/00379727-149-38957
|View full text |Cite
|
Sign up to set email alerts
|

Ethidium Bromide Inhibits Mitochondrial Phosphorylating Oxidation

Abstract: Ethidium bromide (2,7-diamino-9-phenylphenanthridinium-1 0-ethyl bromide) inhibits mitochondria1 DNA (1), RNA (2), and protein syntheses (3, 4). Ethidium bromide can intercalate with the nucleic acids (5) and it is commonly thought that inhibition of these processes occurs by this mechanism rather than by inhibiting ATP generation. Ethidium bromide can combine with mitochondrial membranes (6) producing a color shift in the ethidium spectrum which indicates interaction with a low dielectric site on the membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1978
1978
2014
2014

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Cell treatment with EthBr showed the same outcome on the mitochondrial stress profile as the treatment with SSL. EthBr treatment is used to deplete cells from mtDNA by its ability to inhibit mitochondrial RNA synthesis , but it also directly affects oxidative phosphorylation and ATP synthesis . These different effects of SSL and EthBr versus UVC on mitochondrial function is consistent with the findings of Furda et al who showed that H 2 O 2 , but not the DNA alkylating agent MMS, did cause mitochondrial dysfunction .…”
Section: Discussionsupporting
confidence: 79%
“…Cell treatment with EthBr showed the same outcome on the mitochondrial stress profile as the treatment with SSL. EthBr treatment is used to deplete cells from mtDNA by its ability to inhibit mitochondrial RNA synthesis , but it also directly affects oxidative phosphorylation and ATP synthesis . These different effects of SSL and EthBr versus UVC on mitochondrial function is consistent with the findings of Furda et al who showed that H 2 O 2 , but not the DNA alkylating agent MMS, did cause mitochondrial dysfunction .…”
Section: Discussionsupporting
confidence: 79%
“…Variation in mitochondrial function might reflect the reported variations in the capacities of these tissues for protein and DNA syntheses (2,3). We have already shown that inhibition of protein synthesis in rat liver by ethidium bromide was in part due to inhibition of phosphorylating oxidation in the mitochondria (4).…”
mentioning
confidence: 98%